Bakti Pendidikan Pusat Kesehatan Matematika Sekolah melalui Pelatihan Pembelajaran Etnomatematika Sunda bagi Seluruh Guru dan Siswa SD - Supriadi Supriadi; Tiurlina Tiurlina; Andika Arisetyawan (Universitas Pendidikan Indonesia Kampus Serang, 2021)
The assumption of students and primary school teachers that math learning was difficult and unpleasant as well as unrelated to daily life. Mathematics would be fun if connected to Sundanese culture. Sundanese ethnomathematics learning innovation could be taught to students and elementary school teachers through Sundanese ethnomathematics learning innovation training in their schools. Universitas Pendidikan Indonesia Serang School Mathematics Health Center (Puskesmas) is a community service to Universitas Pendidikan Indonesia community that will perform devotion to students and teachers of elementary school partners PLSP (Field Introduction Education Unit) in State Elementary School 4 of Serang City, Serang District, Banten Province. The output that will be produced from this activity are publications in the journal and publications in mass media. After this program, initially Teacher and student feel happy and easy in mathematics learning with Sundanese culture